CADE X Judiciário: estudo sobre a revisão judicial das decisões do CADE no contexto da globalização - Vieira, Caroline Sanselme (2008)
The scope of the present study is to review the relationship between the Brazilian Competition Law and the Judiciary Branch. Before looking into its core -- which is the revision of CADE s decisions by the judicial courts this study examines the development of Brazilian constitutional and infraconstitutional economic law since its first steps up to current days. Afterwards, it carefully observes the constitutional articles related to the present economic order and the Brazilian Competition Law (Law 8884/94). The Brazilian System of Competition Defense is then thoroughly studied, including its functions, proceedings, rules, and especially the main characteristics of CADE s decisions. The Judiciary Branch is dealt with right after that, under a review that contemplates case laws or decisional opinions, the object of which have been CADE s decisions. Also considered in this study is the review of decisions taken by foreign competition agencies in comparative jurisprudence. The positive and negative aspects of the judicial review are addressed before a conclusion is reached, which consists of proposing some possible solutions to put an end to the legal insecurity caused by this matter in Brazil in light of market globalization